Development of physical and sports specific performance of youth soccer players for the period of one season - Hofer, C.; Wirth, K.; Haller, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The purpose of this study is to reveal possible developments between two performance groups within the same team for the period of one season. It has already been shown that jumping and sprinting abilities can be increased through strength training interventions (Wirth et al., 2011). The aim of this study is to disclose how one different training session influences sports motoric and soccer specific performance parameters although training and match volume keeps the same. Methods: The subjects (n=15; age= 9.17 +- 0,28; sex= 14 m, 1 w) played all for the same team, but participated in different training sessions (2 groups). Once a week the training of the high performance group members was replaced by a session at a performance centre (LAZ) and they were selected by talent scouts of the Austrian Football Association (OEFB). Performance parameters were analysed for Drop Jumps (DJ) from various heights (16,24 and 32 cm), Squat Jumps (SJ), Countermovement Jumps (CMJ), Sprints (10 and 30 Meters), a soccer specific version of the Illinois Agility Tests (IA) and for the Loughborough soccer passing test (LSPT) over 12 weeks (autumn season). Data was analysed with a two-way analysis of variance (ANOVA) with post hoc Test Bonferroni by using the statistics software SPSS (Version 20.0). Results: The study indicated a significant (p<0.05) decrease in sprint performance of both groups over 10 and 30 meters. Regarding repeated measurement factors no interactions for any parameter between the groups has been found over the period of the season. Discussion: Due to no significant varying development of both groups, the one different training session of the high performance group has no influence on the development of the measured performance parameters. Regarding declining sprint times, environmental influences like variable temperature, minimal discrepancies of the light barrier system positioning or the possible error created by the design of the light barrier system (one sensor system) can not be ruled out.